Evaluation of Physical, Chemical, and Microbial Quality of Toned Milk Available in Bangladesh Market - Papry Chakrabortty; Goutam Kumar Debnath; Md Saiful Bari (Food ScienTech Journal, 2025)
Toned milk has been gaining popularity in Bangladesh day by day, but its qualities are yet to be evaluated. The study was conducted to assess the qualities of toned milk of the available brands (Brand A, Brand B, and Brand C) in the local markets of Bangladesh. The physical quality including color and appearance, odor, flavor, and body was evaluated by expert panel members comparing them to the Bangladesh Institute of Standards (BIS). The chemical parameters including acidity, lactose, fat, solids-not-fat (SNF), total solids (TS), and protein contents were evaluated. The microbiological parameters, we evaluated, were the total viable count (TVC) and coliform count of toned milk from different brands. The organoleptic tests revealed toned milk from Brands A and C as good quality (overall score >80), but that from Brand B as fair quality (overall score = 73). The specific gravity, SNF, and TS varied significantly between different brands of toned milk (P < 0.05). The highest specific gravity was in Brand A and Brand C toned milk (both 1.031) and the lowest in Brand B toned milk (1.030). The SNF content was the highest in Brand A toned milk (8.974) and the lowest in Brand B toned milk (8.529). The TS content was the highest in Brand A toned milk (12.174) and the lowest in Brand B toned milk (11.729). However, the specific gravity, SNF and TS were within the BSTI standards range. The fat, acidity percentage, protein, casein and lactose content did not differ significantly (P > 0.05), and possessed a good quality based on the BSTI standards. There were highly significant differences among the total viable count of bacteria of different brands of toned milk (P < 0.01), but the values were within BSTI standards. No coliforms were detected, indicating that good sanitary measures were adopted during manufacture and storage.